2013
DOI: 10.1145/2464526.2464539
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the software testing efficiency by using a genetic algorithm

Abstract: This paper presents a design method for optimizing software-testing efficiency by identifying the most critical path clusters in a program. This is done by the application of soft computing techniques, specifically genetic algorithms. We develop a genetic algorithm that selects the software path clusters to test, which are weighted in accordance with the criticality of the path. Exhaustive software testing is rarely possible because it becomes intractable for even medium-sized software applications. Typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Then, TFIDF is premeditated by. 𝑇𝐹𝐼𝐷𝐹(𝑑) = 𝑑/𝑇 Γ— π‘™π‘œπ‘” 𝑁 /𝑛 𝑑 (21) In which: T = word recurrence in apiece report; t = word recurrence in unique record; N = quantity of term presence totally around the archives; and nt = measure of reports has t word. These 2-string measurements be situated subsequently used for computing the weight and distance of the fake experiment [20].…”
Section: H 2 O Algorithm For Ptcmentioning
confidence: 99%
“…Then, TFIDF is premeditated by. 𝑇𝐹𝐼𝐷𝐹(𝑑) = 𝑑/𝑇 Γ— π‘™π‘œπ‘” 𝑁 /𝑛 𝑑 (21) In which: T = word recurrence in apiece report; t = word recurrence in unique record; N = quantity of term presence totally around the archives; and nt = measure of reports has t word. These 2-string measurements be situated subsequently used for computing the weight and distance of the fake experiment [20].…”
Section: H 2 O Algorithm For Ptcmentioning
confidence: 99%
“…Path coverage in the software testing is always an NP problem with the randomly generated test cases, with the genetic algorithm most paths have been found, the randomly generated test cases divided into different groups for the maximum path coverage. K-means algorithm is used to form different clusters and applied GA to generate the new test cases for maximum path coverage [12,14].…”
Section: Literature Surveymentioning
confidence: 99%
“…The results have shown that GA is more effective and efficient than random testing. Rao et al (2013) designed a methodology for test data generation by using GA to cover the most critical path of a program. Singh (2012) applied GA to generate test data for path coverage.…”
Section: Related Workmentioning
confidence: 99%